(untitled) (REMUNOM, 2025)
Urban growth has not been accompanied by the provision of adequate infrastructure for basic sanitation public services. This situation compromises environmental health, since the absence or deficiency of basic sanitation services contributes to unhealthy environmental conditions. The present study aimed to identify and classify the environmental health of the Búzios do Francês residential subdivision, located in the Porto Grande neighborhood in the municipality of Marechal Deodoro in the state of Alagoas, with the object of analysis being the basic sanitation services provided in the location under study. A bibliographic survey was carried out on environmental health and health indicators, as substantiated in Dias (2003), Gama (2013) and Gama and Almeida (2020); on-site visits to collect health information through observation and interviews with residents; replication of the health indicators adapted by Gama (2013) and to end the tabulation, treatment and processing of the information obtained for the classification of environmental health, taking as reference the literature studied and the local reality. The results obtained showed that the overall environmental health of the subdivision studied is within the low health range. Among the public basic sanitation services in the region studied, water supply and solid waste collection are the two services that present the best situation, while sewage is the service that presents the worst situation. Given this reality, the municipal government is warned to carry out sanitary interventions in the area studied. Keywords: Sanitary Indicator; Health; Basic sanitation.